2013
DOI: 10.1007/s11596-013-1098-7
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably reduced expression of FoxO3a in metaplastic colorectum, primary colorectal cancer and liver metastasis

Abstract: The forkhead family members of transcription factors (FoxOs) are expected to be potential cancer-related drug targets and thus are being extremely studied recently. In the present study, FoxO3a, one major member of this family, was identified to be down-regulated in colorectal cancer through micro-array analysis, which was confirmed by RT-PCR and Western blot in 28 patients. Moreover, immunohistochemistry (IHC) showed that the expression levels of FoxO3a were remarkably reduced in 99 cases of primary colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Although expression levels were noted to differ between AA vs. CA tumors, this decreased expression was not statistically significant. These immunohistochemical results support a recent report of decreased FOXO3a (39) expression in CRC, and suggest that miR-182 levels may contribute to the regulation of FOXO1 and FOXO3a expression. The concept that increased miR-182 levels in AA compared to CA levels may contribute to increased AA colon cancer mortality is further supported by a recent report linking miR-182 to reduced colon cancer survival and increased liver metastases (40).…”
Section: Discussionsupporting
confidence: 90%
“…Although expression levels were noted to differ between AA vs. CA tumors, this decreased expression was not statistically significant. These immunohistochemical results support a recent report of decreased FOXO3a (39) expression in CRC, and suggest that miR-182 levels may contribute to the regulation of FOXO1 and FOXO3a expression. The concept that increased miR-182 levels in AA compared to CA levels may contribute to increased AA colon cancer mortality is further supported by a recent report linking miR-182 to reduced colon cancer survival and increased liver metastases (40).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated a negative association between FoxO3a, and cancer grade and spread. In ovarian cancer, liver cancer, breast cancer and prostate cancer, FoxO3a expression is decreased (8,(21)(22)(23). In addition, the nuclear transport and abnormal cytoplasmic distribution of FoxO3a is associated with poor prognosis of breast cancer (9).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer, prostate cancer, gliomas, and CRC have all been associated with the dysregulated expression of FOXO3 [12][13][14][15][16]. In metaplastic colorectum, liver metastasis, and primary CRC, loss or reduced expression of FOXO3 has been observed [17].…”
Section: Introductionmentioning
confidence: 99%